Implementasi Budaya 5S (Senyum, Sapa, Salam, Sopan, Santun)Terhadap Pembentukan Karakter Siswa dan Nilai Kesopanan Siswa SD IT Al Minah - Rahmayani, Ulina; Ndona, Yakobus; Saragi, Daulat (EDUTECH, 2025)
This research seeks to investigate the application of the 5S culture (Smile, Greet, Greeting, Polite, Courteous) and its impact on the development of character and values of politeness among students at SD IT Al Minah.  This study employs a descriptive qualitative research method to investigate the significance and effects of implementing the 5S culture within the educational setting.  The findings of the study suggest that the execution of the 5S culture operates efficiently through a cohesive and systematic habituation process, propelled by the proactive engagement of teachers as role models.  This process profoundly influences the development of more commendable student characteristics, particularly regarding religiosity, social consciousness, and a sense of responsibility.  Furthermore, the 5S culture has demonstrated efficacy in enhancing students' values of politeness by translating the abstract notion of "politeness" into tangible actions that can be readily implemented in daily social interactions.  In summary, the implementation of the 5S culture through habituation and exemplary figures has effectively contributed to the development of character and the reinforcement of politeness values among students at SD IT Al Minah